The role of face-to-face meetings in technology-supported self-organizing distributed teams - Kevin Crowston; James Howison; Masango, Chengetai; Eseryel, U. Yeliz (IEEE Transactions on Professional Communications, 2007)
We examine the role of face-to-face meetings in the context of technology-supported self-organizing distributed or virtual teams, specifically Free/Libre Open Source Software (FLOSS) development teams. Based on a qualitative inductive analysis of data from interviews and observations at FLOSS conferences, we identify a variety of settings in which developers meet face-to-face, activities performed in these settings and benefits obtained. Contrary to the conventional wisdom, FLOSS developers generally do not meet face-to-face until the project is well under way. An additional benefit of face-to-face meetings is time away from a regular job and speed of interaction for certain kinds of tasks.
Keywords: FLOSS